Altered Hippocampal Synaptic Potentiation in P2X(4) Knock-Out Mice - Sim, Joan A. (J Neurosci, 2006)
P2X(4) purinergic receptors are calcium-permeable, ATP-activated ion channels. In the CA1 area of the hippocampus, they are located at the subsynaptic membrane somewhat peripherally to AMPA receptors. The possible role of P2X(4) receptors has been difficult to elucidate because of the lack of selective antagonists. Here we report the generation of a P2X(4) receptor knock-out mouse and show that long-term potentiation (LTP) at Schaffer collateral synapses is reduced relative to that in wild-type mice. Ivermectin, which selectively potentiates currents at P2X(4), was found to increase LTP in wild-type mice but had no effect in P2X(4) knock-out mice. We suggest that calcium entry through subsynaptic P2X(4) receptors during high-frequency stimulation contributes to synaptic strengthening.